Effect of different types of physical training on gymnastics jump height: meta-analysis - Ulloa-Sánchez, Paul (2021)
The main objective of this study was to determine the effect of different types of physical training on gymnastics jump height under the meta-analysis methodology. The PRISMA guidelines were followed. The electronic databases used in the search were EBSCOhost (SPORTDiscus, MEDLINE, Academic Search Complete, E-Journals, OmniFile Full Text Select (HW Wilson), Web of Science, Scopus, SciencDirect, Research Gate, and Pubmed in order to identify relevant articles regarding the use of physical training and the assessment of jump height in gymnasts before and after intervention. Based on the inclusion criteria, 29 individual studies and 157 individual effect sizes (TE) were coded. The total sample included 688 gymnasts. The overall TE of the experimental group was low to moderate and significant (TE = 0.33, p < 0.001*). A significant difference was evidenced (p = 0.001*) between the types of training. The Post Hoc analysis showed that the global TE of plyometrics training (TE = 0.85, p < 0.001*) was higher than that of stretching (TE = -0.07, p = 0.56) and “others” (TE = 0.48, p < 0.001*), but not than vibration (TE = 0.54, p < 0.001*). Furthermore, the overall TE of stretching was significantly lower than all the other types of training. It was concluded that the type of training with the highest overall TE was plyometrics, followed by vibrational platform training. Stretching does not appear to be significantly related to gymnastics jump height.